Differential phosphorylation of Clr4SUV39H by Cdk1 accompanies a histone H3 methylation switch that is essential for gametogenesis. (21st November 2022) - Kuzdere, Tahsin; Flury, Valentin; Schalch, Thomas; Iesmantavicius, Vytautas; Hess, Daniel; Bühler, Marc
Abstract: Methylation of histone H3 at lysine 9 (H3K9) is a hallmark of heterochromatin that plays crucial roles in gene silencing, genome stability, and chromosome segregation. In Schizosaccharomyces pombe, Clr4 mediates both di‐ and tri‐methylation of H3K9. Although H3K9 methylation has been intensely studied in mitotic cells, its role during sexual differentiation remains unclear. Here, we map H3K9 methylation genome‐wide during meiosis and show that constitutive heterochromatin temporarily loses H3K9me2 and becomes H3K9me3 when cells commit to meiosis. Cells lacking the ability to tri‐methylate H3K9 exhibit meiotic chromosome segregation defects. Finally, the H3K9 methylation switch is accompanied by differential phosphorylation of Clr4 by the cyclin‐dependent kinase Cdk1. Our results suggest that a conserved master regulator of the cell cycle controls the specificity of an H3K9 methyltransferase to prevent ectopic H3K9 methylation and to ensure faithful gametogenesis. Synopsis: Upon entry into meiosis, Cdk1 is inhibited, Clr4 SUV39H is no longer phosphorylated and its substrate histone H3 transitions from H3K9me2 to H3K9me3, which is critical for faithful chromosome segregation during meiosis. Constitutive heterochromatin temporarily transitions from H3K9me2 to H3K9me3 when fission yeast cells commit to meiosis. The meiotic H3K9 methylation switch is accompanied by differential phosphorylation of Clr4, which depends on the cyclin‐dependent kinase Cdk1. Monopolar spindle attachment of sister chromatids critically depends on H3K9me3 at the first meiotic division. Abstract : Upon entry into meiosis, Cdk1 is inhibited, Clr4 SUV39H is no longer phosphorylated and its substrate histone H3 transitions from H3K9me2 to H3K9me3, which is critical for faithful chromosome segregation during meiosis.